Methanotrophic community dynamics in a seasonally anoxic fjord: Saanich Inlet, British Columbia - Torres-Beltrán, Mónica; Hawley, Alyse K.; Capelle, David W.; Bhatia, Maya P.; Durno, Evan W.; Tortell, Philippe D.; Hallam, Steven J. (Frontiers in Marine Science, 2016)
Marine oxygen minimum zones (OMZs) play disproportionate roles in nutrient and climate active trace gas cycling including nitrous oxide and methane, in the ocean. OMZs are currently expanding due to climate change making it increasingly important to identify microbial controls on trace gas cycling at the individual, population and community levels. Here we present a two-year survey of the microbial community along seasonal redox gradients in Saanich Inlet focused on identifying microbial agents driving methane oxidation. Although methanotrophs were rare, we identified three uncultivated groups affiliated with particulate methane monooxygenase (pMMO) encoding phylogenetic groups (OPU), and methanotrophic symbionts as primary drivers of methane oxidation in Saanich Inlet. Distribution and activity patterns for these three groups were consistent with niche partitioning that became increasingly resolved during water column stratification. Moreover co-occurrence analysis combined with multi-level indicator species analysis revealed significant correlations between operational taxonomic units affiliated with Methylophaga, Methylophilales, SAR324, Verrucomicrobia, and Planctomycetes with OPUs and methanotrophic symbiont groups. Taken together these observations shed new light on the composition, dynamics, and potential interspecific interactions of microbes associated with CH4 cycling in the Saanich Inlet water column, provide a baseline for comparison between coastal and open ocean OMZs and support the potential role of OPUs, and methanotrophic symbiont groups as a widely distributed pelagic sink for CH4 along continental margins.